Deciphering the genetic basis of root morphology, nutrient uptake, yield, and yield-related traits in rice under dry direct-seeded cultivation systems - Sandhu, Nitika; Subedi, Sushil Raj; Singh, Vikas Kumar; Sinha, Pallavi; Kumar, Santosh; Singh, S.P.; Ghimire, Surya Kant; Pandey, Madhav; Yadaw, Ram Baran; Varshney, Rajeev K.; Kumar, Arvind (Springer, 2019)
In the face of global water scarcity, a successful transition of rice cultivation from puddled to dry direct-seeded rice (DDSR) is a future need. A genome-wide association study was performed on a complex mapping population for 39 traits: 9 seedling-establishment traits, 14 root and nutrient-uptake traits, 5 plant morphological traits, 4 lodging resistance traits, and 7 yield and yield-contributing traits. A total of 10 significant marker-trait associations (MTAs) were found along with 25 QTLs associated with 25 traits. The percent phenotypic variance explained by SNPs ranged from 8% to 84%. Grain yield was found to be significantly and positively correlated with seedling-establishment traits, root morphological traits, nutrient uptake-related traits, and grain yield-contributing traits. The genomic colocation of different root morphological traits, nutrient uptake-related traits, and grain-yield-contributing traits further supports the role of root morphological traits in improving nutrient uptake and grain yield under DDSR. The QTLs/candidate genes underlying the significant MTAs were identified. The identified promising progenies carrying these QTLs may serve as potential donors to be exploited in genomics-assisted breeding programs for improving grain yield and adaptability under DDSR.